Influence of baking time and formulation of part-baked wheat sourdough bread on the physical characteristics, sensory quality, glycaemic index and appetite sensations - Temkov, Mishela; Rocha, João Miguel; Rannou, Cécile; Ducasse, Maren; Prost, Carole (Frontiers in Nutrition, 2024)
Raw materials and process parameters in bread production can modulate the glycemic index, which on itself has been linked with provision of better hunger satisfaction and maintaining better satiation. The objective of this research was to investigate if using unrefined wheat flour or the addition of intact cereals in formulation or alternating the baking time would have an effect on physical characteristics, sensory quality, glycaemic index and appetite sensations in wheat sourdough bread. In the study, three types of commercial pre-baked frozen sourdough bread, baked to the final baking for two different times (long and short baking time) were used. A randomized controlled crossover trial was performed with 10 healthy adults who consumed sufficient quantity of bread to ingest 50 g available carbohydrates. Participants self-reported appetite sensations (desire to eat, hunger, fullness, satisfaction, appetite) on a 10 cm visual analogue scale (VAS) scale in a course of 180 min. In addition, bread products were subjected to overall acceptability and different sensory attributes were examined on JAR "just about right" scale. Different bread formulations (unrefined wheat flour, cereal flour or intact cereals) and different length of baking time significantly influenced (p˂0.005) physical, textural and sensory features of products. The alternation of aforementioned parameters decreased the glycemic index, but not significa ntly (p˃0.005). No correlation was found between lower GI, satiety and satiation. Liking score and incremental area under the curve (iAUC) of satiety and satiation were calculated as highest in sourdough bread with added cereals.